Body composition and eating habits of workers with normal day and shift work. (24th June 2020) - Martins, A; Lima, J
Abstract: Introduction Recently, shift work and it consequences have been studied due to the strong relationship between shift work, sleep disorders and unhealthy eating habits, which could influence body composition and related health problems. Objectives To analyse the influence of shift work on body composition and eating habits of workers. Methodology Data collection was carried out through an interview with employees from a company in which data were collected such as sex, age, average number of hours of sleep and work schedule. An anthropometric evaluation was performed and weight, body fat mass percentage and waist circumference were measured. The height was self-reported. Individuals were also asked to answer to a semi-quantitative food frequency questionnaire. Data analysis was performed with descriptive and statistical analysis using U-Mann-Whitney test, in the IBM SPSS Statistics 25 program. Results The final sample consisted of 20 shift workers and 20 normal day workers. The mean BMI of normal day workers was 23.54 ± 3.19 kg/m2, and the average of the shift workers was 27.97 ± 5.48 kg/m2 (p = 0, 001). Regarding the percentage of fat mass, the mean of the normal day sample was 28.53 ± 6.30% and the shift work sample showed an average of 29.85 ± 8.54% (p = 0, 841). The shift sample reported a higher average daily intake of processed foods, high energy density food products with high fat and sugar content. Conclusion The higher BMI and fat percentage observed in shift workers comparing to normal day works are a topic of concern and could contribute to the assumption that the dynamics required by shift work can lead to changes in circadian rhythm, leading to metabolic alterations that could influence body composition and dietary choices.